2014
DOI: 10.1186/s12888-014-0268-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in schizophrenia: a case-control study on the effects on social cognition and neurocognition

Abstract: BackgroundSchizophrenia is a debilitating mental disorder that presents impairments in neurocognition and social cognition. Several studies have suggested that the etiology of schizophrenia can be partly explained by oxidative stress. However, our knowledge about the implications of oxidative stress on illness-related cognitive deficits is still far from being clear. The aim of this work was to study the role of oxidative stress molecules on social cognition and neurocognition in patients with schizophrenia.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 69 publications
(65 reference statements)
1
48
2
Order By: Relevance
“…While the 26S proteasome is usually considered more efficient than these other complexes, both uncapped 20S CP and the IP have been shown to be more capable of degrading oxidized proteins (Pickering et al, 2010). Markers of increased oxidative stress such as increased lipid peroxidation, reactive oxygen species, and decreased antioxidant levels have been observed in postmortem brain in schizophrenia (Bošković et al, 2011;Gonzalez-Liencres et al, 2014;Reyazuddin et al, 2014;Rajasekaran et al, 2015). This may suggest that, in schizophrenia, there is an environment of oxidative stress, which would lead to the recruitment of the IP and 11S αβ RP in response to the increased oxidative load.…”
Section: Discussionmentioning
confidence: 99%
“…While the 26S proteasome is usually considered more efficient than these other complexes, both uncapped 20S CP and the IP have been shown to be more capable of degrading oxidized proteins (Pickering et al, 2010). Markers of increased oxidative stress such as increased lipid peroxidation, reactive oxygen species, and decreased antioxidant levels have been observed in postmortem brain in schizophrenia (Bošković et al, 2011;Gonzalez-Liencres et al, 2014;Reyazuddin et al, 2014;Rajasekaran et al, 2015). This may suggest that, in schizophrenia, there is an environment of oxidative stress, which would lead to the recruitment of the IP and 11S αβ RP in response to the increased oxidative load.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed an increased homocysteine concentration in biological fluids in children/adolescents with ASD compared to age-matched TD controls (Paşca et al, 2006;Adams et al, 2011;Ali et al, 2011;Kałuzna-Czaplińska et al, 2011;Tu et al, 2012), however other failed to find such difference (James et al, 2004). Evaluation of the relationship between homocysteine and the clinical features and severity of core symptoms in patients with ASD may help to shed some light on the role of this unusual amino acid in the symptomatology of the disorder and ultimately to identify any possible links between specific neuropsychiatric alterations and the common pathophysiological changes present in this disease (Parellada et al, 2012;Gonzalez-Liencres et al, 2014). Finally, identifying differential biomarkers of a single core symptom of ASD could be very helpful in pinpointing specific mechanisms responsible for the phenotype and may help tailor new pharmacological for children with ASD with this biochemical alteration.…”
Section: Introductionmentioning
confidence: 95%
“…This was consistent with the research conducted by Asoglu et al (2016), who found that an increase in cytokines as an inflammatory factor was strongly associated with inhibition of erythrocyte maturation by erythropoietin, which was reflected by an increase in the RDW value. Another study conducted by Zhang et al 2009; Boskovic and Vovk (2008); and Gonzalez et al (2014), about RDW had shown a direct relationship between damage of blood cells in the circulation due to high oxidative stress and the increase of RDW values. Whereas Miller and Kirkpatrick (2013) found that pro-inflammatory cytokines, as well as oxidative stress, contribute to an increase in the RDW value in schizophrenia.…”
Section: Resultsmentioning
confidence: 94%